Competitiveness Challenges and Opportunities in Light of the Draghi Report - Juhász, Péter (Public Finance Quarterly, 2024)
Competitiveness has become a central theme in economic policy discussions, reﬂecting the need for nations, businesses, and individuals to adapt to an increasingly interconnected global economy. Initially applied in corporate strategy, the concept has expanded to national and supranational contexts. This article explores the theoretical and practical dimensions of competitiveness by analysing its implications at diﬀerent levels – countries, corporations, and individuals – while reﬂecting on the European Union’s evolving competitiveness strategy, particularly in light of the Draghi Report (2024). This report urges EU member states to adopt cohesive policies addressing challenges such as technological innovation, energy costs, and demographic shifts. The study responds to this call by exploring how competitiveness manifests across these levels and the conﬂicts that may arise when pursuing this objective.The ﬁndings highlight that the pursuit of competitiveness at the national, corporate, and individual levels is interconnected and conﬂicting. While the EU’s uniﬁed competitiveness agenda oﬀers a framework for strengthening its global economic standing, its success depends on recognizing and addressing each member state’s unique challenges and potentials. A balanced, inclusive, and adaptive policy approach can enhance competitiveness while ensuring long-term economic resilience and social cohesion.